ChemInform Abstract: Formal Asymmetric [4 + 1] Annulation Reaction Between Sulfur Ylides and 1, 3‐Dienes. Issue 3 (29th December 2015) - Rousseau, Olivier; Delaunay, Thierry; Dequirez, Geoffroy; Trieu‐Van, Tran; Robeyns, Koen; Robiette, Raphael
Abstract: Functionalized cyclopentenes are conveniently obtained via stereoselective cyclopropanation reaction of sulfur ylides with 1, 2‐dienes followed by in situ stereospecific MgI2 ‐promoted rearrangement of vinylcyclopropanes.